2020
DOI: 10.1111/jdi.13324
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet strategy in primary and secondary prevention of cardiovascular disease in patients with type 2 diabetes mellitus: A perspective from the guideline appraisal

Abstract: Aims/Introduction: To appraise guidelines on the antiplatelet strategy of prevention of cardiovascular disease (CVD) in patients with type 2 diabetes mellitus, and highlight the consensuses and controversies to aid clinician decision-making. Materials and Methods: A systematic search was carried out for guidelines regarding CVD prevention or focusing on type 2 diabetes patients. Appraisal of Guidelines for Research and Evaluation II instrument was utilized to appraise the quality of included guidelines. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A large sample investigation involving 584 participants revealed that compared to non-T2D participants, T2D patients suffer from more severe carotid atherosclerotic stenosis, appearing as larger lipid necrosis cores with increasing calcification ( 66 ). T2D patients are extremely susceptible to CVD, which has become the most common cause of death in T2D ( 67 ). Similar to other metabolic diseases, T2D shares several pathological factors with atherosclerosis.…”
Section: Anti-atherosclerotic Role Of Tcf7l2 In Metabolic Balancementioning
confidence: 99%
“…A large sample investigation involving 584 participants revealed that compared to non-T2D participants, T2D patients suffer from more severe carotid atherosclerotic stenosis, appearing as larger lipid necrosis cores with increasing calcification ( 66 ). T2D patients are extremely susceptible to CVD, which has become the most common cause of death in T2D ( 67 ). Similar to other metabolic diseases, T2D shares several pathological factors with atherosclerosis.…”
Section: Anti-atherosclerotic Role Of Tcf7l2 In Metabolic Balancementioning
confidence: 99%
“…Although statistically non-significant, there was a trend of increased HR of the patients under antiplatelet therapy. This implies that many of the clinicians in Taiwan still over-used antiplatelet medication in primary-prevention patients, although recently published guidelines did not recommend routine prescription of antiplatelets for primary prevention [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no clinical study of fibrates in the treatment of T2DM complicated by HF. Antiplatelet agents help to improve islet survival and function, islet graft outcome, and insulin gene expression [117][118][119][120]. However, platelet reactivity is enhanced in patients with insulin resistance, and the risk of thrombosis and bleeding should be taken into account.…”
Section: Targeting Insulin Resistance In Dhdmentioning
confidence: 99%